Perencanaan Kantor Bupati Mandau Dengan Pendekatan Transformasi Arsitektur Melayu - Harun Alrasyid Alvino; Agus Basri; Hendri Silva (JURNAL TEKNIK, 2020)
Duri is the district capital Mandau, Bengkalis, Riau, Indonesia. With a population of about 239.361 inhabitants were ditahap expansion of Bengkalis district to become a municipality. Responding to the expansion that has been moving dihimbaukan still very volatile and has a formation in the society. In the framework of the expansion, the community is very enthusiastic in mengupakan Duri Duri city became municipality. Even if they wanted to be taken to the point best, only the expansion movement had managed to move the working area of ​​the Regent of Bengkalis City Duri. The purpose of the planning office of regent saber planning objective to produce a Planning and progaming in the design office of mayor, with levels of Riau province, while the subjective goal to generate a spatial plan / program that is able to accommodate the activities of managers, especially users and other activities. Planning office of regent Saber with pendekata Malay architectural transformation is planned in the Clean Water Pipe Road, Duri Riau, namely where the location away from the noise, thus making the office feel comfortable and calm when in office. The concept of this saber regent office planning with pendekata "Malay architecture" in which the planning concepts using the basic concept design principle customize the theme Shape Transformation with Malay architecture. To form the building using subtractive transformation types and customize the design basis Malay Architecture